Combined anterior and posterior instrumentation in severe and rigid idiopathic scoliosis - Bullmann, Viola (Springer-Verlag, 2006)
A prospective clinical and radiographic evaluation of 33 consecutive patients with severe and rigid idiopathic scoliosis (average Cobb angle 93°, flexibility on bending films 23%) were treated with combined anterior and posterior instrumentation with a minimum follow-up of 2 years. All patients underwent anterior release and VDS-Zielke Instrumentation of the primary curve. In highly rigid scoliosis, this was preceded by a posterior release. Finally, posterior correction and fusion with a multiple hook and pedicle screw construct was performed. Thirty patients were operated in one stage, three patients in two stages. Preoperative curves ranged from 80 to 122° Cobb angle. Frontal plane correction of the primary curve averaged 67% with an average loss of correction of 2°. The apical vertebral rotation of the primary curve was corrected by 49%. In all but three patients, sagittal alignment was restored. There were no neurological complications, deep wound infections or pseudarthrosis. Combined anterior and posterior instrumentation is safe and enables an effective three-dimensional curve correction in severe and rigid idiopathic scoliosis.